Implementation of sugeno fuzzy method on bandwidth management at STMIK YMI Tegal - Gunawan Gunawan; Wresti Andriani; Dodi Setiawan (Institute of Computer Science (IOCS), 2023)
In the lecture process, the Internet becomes very important, and access settings or bandwidth management is needed so that Internet use can run smoothly. Many users can cause the burden of computer access to be high, so internet use will be unbalanced if bandwidth management is not carried out. Bandwidth management aims to allocate bandwidth in an internet network so that the distribution is equal and the comfort between users and one another is not disturbed. The method used is fuzzy Sugeno to implement Sugeno's fuzzy logic into bandwidth management and optimize internet usage. Fuzzy inputs used include download, streaming, and browsing variables. Using three fuzzy sets, namely low, standard, and solid. The output is Download Limit, Streaming Limit, and Browsing Limit. System testing will be conducted using MATLAB. After testing, results were obtained through bandwidth limits from downloading, streaming, and browsing. One of the study's results included a given system input download = 700, streaming = 668, and browsing = 611. Produce output is Download Limit = 700, Streaming Limit = 481, and Browsing Limit = 319